Extending opera-artist-led explorations in operatic practice through interactivity and electronics - Unander-Scharin, Carl (Stockholm KTH vetenskap och konst, 2014)
How can we re-empower opera singers, extending their control over accompaniment and vocal expressivity? To answer this question, I have opened a novel design space, Extending Opera, consisting of interactive artistoperated tools to be used on-stage. The research has its methodological groundings in Research through Design (RtD) and Research through the Arts (RttA). This particular method is coined "research-through-the-art-form-opera" as I have worked within the realms and traditions of opera, probing its boundaries by designing, researching and creating through its own artistic toolbox. Originally conceived for personal use, the artifacts were later used by other singers and incorporated in performances of opera in small and large scale. By composing and designing for the requirements in operatic productions, high demands on robustness were explored in and through custom-built interfaces.The work resulted in ten novel artifacts and performances exploring the expressivity of these tools. Extending Opera is guided by and probed through three questions:1. How can the design and creation of interactive, artist-operated instruments be informed by deep musical knowledge and be probed by the particular conditions surrounding an operatic production?2. What impact can interactive, artist-operated instruments have on the opera singers themselves and on their vocal technique?3. How can interactive, artist-operated instruments empower opera singers, thus challenging contemporary power hierarchies thereby reconnecting to the explorative practice in opera's early days? My knowledge contribution has surfaced through artistic practice and consists of the exemplars and the artworks, as well as three abstractions one procedure, one requirement and one experiential quality.